Ocular Irritation and Contact Lenses - Backman, Howard A (Canadian Journal of Optometry, 1982)
A number of causes of ocular irritation from the use of hydrogel lenses are examined in relation to the onset of G. P. C., kerato conjunctivitis, keratitis and infiltrative conjunctivitis.